Ventromedial prefrontal cortex damage alters resting blood flow to the bed nucleus of stria terminalis. (March 2015) - Motzkin, Julian C.; Philippi, Carissa L.; Oler, Jonathan A.; Kalin, Ned H.; Baskaya, Mustafa K.; Koenigs, Michael
Abstract: The ventromedial prefrontal cortex (vmPFC) plays a key role in modulating emotional responses, yet the precise neural mechanisms underlying this function remain unclear. vmPFC interacts with a number of subcortical structures involved in affective processing, including the amygdala, hypothalamus, periaqueductal gray, ventral striatum, and bed nucleus of stria terminalis (BNST). While a previous study of non-human primates shows that vmPFC lesions reduce BNST activity and anxious behavior, no such causal evidence exists in humans. In this study, we used a novel application of magnetic resonance imaging (MRI) in neurosurgical patients with focal, bilateral vmPFC damage to determine whether vmPFC is indeed critical for modulating BNST function in humans. Relative to neurologically healthy subjects, who exhibited robust rest-state functional connectivity between vmPFC and BNST, the vmPFC lesion patients had significantly lower resting-state perfusion of the right BNST. No such perfusion differences were observed for the amygdala, striatum, hypothalamus, or periaqueductal gray. This study thus provides unique data on the relationship between vmPFC and BNST, suggesting that vmPFC serves to promote BNST activity in humans. This finding is relevant for neural circuitry models of mood and anxiety disorders.